De-colonising My Trans Body: Fanon and the masks I have worn (Existential Analysis: Journal of the Society for Existential Analysis, 2021)
Drawing on the works of Beauvoir, Sartre and Fanon, I conceptualise my trans body's colonisation, both by the mental health professions involved in my transition, and by Queer Theory's appropriation of it to demonstrate the performativity of gender. I invite the reader to consider how activism might be used in therapy with trans people.
Keywords: Trans; transgender; pathologisation; queer theory; beyond the binaries